Determining the Methods of Implementing the Individual Development Program of Music Teachers (Eurasian Journal of Research, Development and Innovation, 2022)
This article analyzes the methods of designing the individual development program of music teachers, the problems encountered in the design, setting goals in the development project, and methodological aspects of its implementation